Epidemiologia molecular do papilomavírus humano em uma amostra de mulheres do estado de Alagoas - Santos Filho, Moezio de Vasconcellos Costa (2012)
The Human Papillomavirus (HPV) is a virus of the Papillomaviridae family and its genome consists of DNA. It is the main cause of viral sexual transmission. Cervical cancer or uterine colon cancer is the second most common occurrence among women worldwide. Recent studies have proven that some types of HPV are mainly responsible for the development of this type of cancer. In accordance to its oncogenic activity this viral group was divided in low and high risk types. Brazil does not have a representative amount of data related to the prevalence of HPV infection. The incidence data of the virus is obtained through the analysis of carriers of the invasive carcinoma of uterine colon, cervical intraepithelial neoplasias, and others types of infections associated. Molecular assays have been showing throughout the years an excellent sensitivity and specificity in the detection of the HPV’s DNA. Nowadays, in situ hybridization techniques are being used as method of choice for the detection of the viral DNA. In many studies, the Polymerase Chain Reaction (PCR) with the application of the primers MY09 and MY11 have shown efficiency in viral tracking, consequently, the development of molecular diagnostics allow monitoring of the disease, decreasing mortality rates caused by cancer of the cervix. The DNA sequencing is an efficient methodology used for the molecular characterization of the viral types, which allows the accomplishment of the alignment for similarity of the sequences obtained through others that were already identified and deposited in the GenBank. The current study’s purpose was to identify the different types of HPV and the presence of co-infections through PCR and sequencing of a hyper-variable region of the L1 gene. The studied sample consisted of 515 female volunteers, which 111 (21.55%) presented the incidence of the HPV DNA. Within the acquired specimens, 50% were considered high oncogenic risk (the major incidence was types 16 and 58) and 7.21% had multiple infection. The determination of the base sequencing of the L1 gene is essential to the identification of the viral type. However, the sequencing of the complete gene and both DNA chains become financially unviable for the majority of the specialized laboratories. A practical approach applied in this study was to determine the sequencing of a specific region of the L1 gene with 450pb, where the identification of the HPV became possible by following this methodology. The techniques used showed the necessity of the application of a more sensible and specific viral diagnosis, which contributes to the viral infection control and to the reduction of the mortality rate caused by cervical cancer.